1999
DOI: 10.1902/jop.1999.70.3.294
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A Regulates Interleukin‐1ßand Interleukin‐6 Expression in Gingiva: Implications for Gingival Overgrowth

Abstract: Background: Gingival overgrowth is a common side effect following the administration of cyclosporin A (CsA); however, the cellular mechanisms remain poorly understood. CsA's immunosuppressant properties involve the regulation of synthesis and cellular response to cytokines. A CsA‐induced alteration in the cytokine profile within gingival tissue could provide a mechanism for gingival hyperplasia. The aim of this study was to investigate the effects of CsA on the production of 2 cytokines — interleukin‐1ß(IL‐1ß)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
1
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 45 publications
4
57
1
4
Order By: Relevance
“…22,23,[52][53][54] TGF-β1 and IL-6 are recognized as key mediators responsible for the accumulation of extracellular matrix in both drug-induced gingival overgrowth and HGF. 7,25,[55][56][57][58][59] It has been observed that, in vitro, TGF-β1 and IL-6 upregulate collagens, fibronectins, and laminins in a variety of cell types. 60 However, increased synthesis does not necessarily lead to extracellular matrix accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…22,23,[52][53][54] TGF-β1 and IL-6 are recognized as key mediators responsible for the accumulation of extracellular matrix in both drug-induced gingival overgrowth and HGF. 7,25,[55][56][57][58][59] It has been observed that, in vitro, TGF-β1 and IL-6 upregulate collagens, fibronectins, and laminins in a variety of cell types. 60 However, increased synthesis does not necessarily lead to extracellular matrix accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that CsA affects gingival fibroblast proliferation, 38 promotes abnormal synthesis of collagen and other extracellular matrix molecules, 39 decreases collagen turnover by inhibiting collagen phagocytosis and collagen degrading enzymes, 40,41 and also appears to act on abnormal cytokine production. 42,43 Although the exact mechanism by which CsA induces gingival overgrowth remains unclear, our understanding of the biochemical mechanisms involved in producing these tissue alterations is evolving. For example, increased TGF-β1 production has recently been demonstrated in CsAinduced gingival overgrowth 44 as well as in other fibrotic side effects of CsA-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Some hypotheses have suggested the role of factors such as 1) fibroblasts [2732], 2) inflammatory cytokines [30, 3336], and 3) matrix metalloproteinase (MMP) synthesis [31]. CsA, nifedipine, and phenytoin promote the modeling of periodontal fibroblasts through the synthesis of gingival fibroblasts or inhibition of the decomposition of gingival fibroblasts [2731].…”
Section: Discussionmentioning
confidence: 99%